IMPACT OF TRANSLATION TECHNIQUES ON CHARACTERIZATION AND SUBTITLE QUALITY IN THE GOOD DOCTOR (2017) - Amanda, Putri; Dewi, Ida Kusuma; Sawardi, F. X. (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This qualitative study examines a key challenge in Audiovisual Translation (AVT): balancing technical constraints with the stylistic fidelity required to represent characters with distinctive communicative traits, focusing on Dr. Shaun Murphy, a character with Autism Spectrum Disorder (ASD) in The Good Doctor (2017). The study analyzes English source dialogues and their Indonesian subtitles across seasons 1–4, employing a descriptive qualitative method with a stylistic approach. The analysis identifies the types and functions of repetition, the translation techniques used, and subtitle quality based on accuracy, acceptability, and readability. Expert focus group discussions were conducted to validate the findings. Results show that deletion, reduction, and discursive creation frequently remove repetitions, reducing emotional nuance and weakening ASD-related speech features, thus diminishing character distinctiveness. Conversely, preserving repetitions maintains character integrity and enhances subtitle quality. Theoretically, this study contributes to AVT by highlighting the importance of stylistic fidelity in translating neurodivergent discourse and recognizing repetition as a marker of character identity. Practically, the findings underscore the need for preservation-oriented techniques to prevent character erasure and to support authentic representation of ASD characters.